Phylogenetic analysis and genotype distribution of Hepatitis B Virus (HBV) in Roraima, Brazil - Sousa, Débora Dinelly de; Silva, Claudiane Raquel de Sousa; Lima Junior, Wilson Pereira; Barros, Jacqueline de Aguiar; Nascimento, Ismael Alexandre da Silva; Souza, Victor Costa de; Naveca, Felipe Gomes; Granja, Fabiana (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Hepatitis B virus (HBV) infection is a serious global health problem. HBV has a high viral genetic diversity, with 10 genotypes recognized. In Brazil, the Roraima State is the third in the Northern region regarding the number of hepatitis B cases. On the other hand, few data on HBV genotyping and phylogenetic analysis are available. The purpose of this study is to characterize the HBV genotypes circulating in Roraima State. Of the 113 chronic hepatitis B patients enrolled in this study, 40 were HBV-DNA positive. A fragment of 280 bp (S gene) was amplified by PCR and submitted to nucleotide sequencing. A dataset containing the viral sequences obtained in this study, plus 130 obtained from GenBank was used for genotyping by phylogenetic analysis. The HBV subgenotype distribution found was A1 (62.5%), A2 (7.5%), D2, D3, D4 (2.5%), F2a (12.5%), and F3 (10%). We characterized the genotypes and subgenotypes of HBV circulating among patients in the State of Roraima. In addition, our study shows for the first time the HBV/F3 genotype circulating in Brazil. In conclusion, our findings showed a high diversity of HBV genotypes in Roraima, which is also found in other Brazilian geographical regions.